Relative age effect of female and male handball players participating in Olympics Games Tokyo 2020 - Krawczyk, P.; Dyjas, A.; Szelag, A.; Cedro, M. (Baltic Journal of Health and Physical Activity, 2023)
Introduction: The aim of this study was to determine whether the relative age effect (RAE) was present among handball players participating in the Tokyo 2020 Olympics.